Seinfeld. Season 7 [videorecording (DVD)] - David, Larry; Seinfeld, Jerry; Louis-Dreyfus, Julia; Alexander, Jason, 1959-; Richards, Michael, 1949- (Seinfeld, 2006)
Jerry, a comedian, and his neurotic best friends - Elaine, George, and Kramer - go through everyday life, discussing various quirky situations that we can all relate to (especially if we live in New York). The eccentric personalities of the offbeat characters who make up Jerry's social circle contribute to the fun.